(untitled) (Geo-Eco-Marina, 2020)
This paper summarizes the results of a sedimentologic investigation of Albian sandstones and conglomerates from the eastern extremity of the Southern Carpathians, the area between the Ialomița and Dâmbovița rivers. Lithofacies analysis, paleotransport, provenance and paleoenvironment of these clastic sediments are the main focus of the paper. An important component of the study is the part played by Ialomița-Dâmbovița Albian sediment accumulation in the Albian sedimentary history of the Carpathian Bend zone. Two major lithofacies occur in the Ialomița-Dâmbovița Albian sedimentary succession: medium- and coarse-grained sandstones and sandstones with conglomerate interbeds. These deposits are intercalated with a third significant lithofacies, rhythmic finer grained deposits of silty clay and silty and finegrained sandstones. Some of the coarser grained Albian sediments (both sandstones and conglomerates) are structureless, poorly sorted, have a relatively large amount of sandy matrix and include oversize clasts, features indicative of accumulation by sediment gravity flow. The normal graded sandstones and the conglomerates with poor sorting, abundant matrix and oversize clasts suggest sediment transport by high density turbidity currents. The accumulation of the rhythmic, alternating silty clay and silty fine-grained arenite sediments is ascribed to low density turbidity currents. According to their relationship with the underlying, younger deposits, the monocline structure and their presence within a succession of clastic sediments forming a coarsening-upward stacking pattern, it is proposed here that the Albian deposits in the Ialomița-Dâmbovița area were involved in a very active, large-scale progradation process, with deposition occurring on the continental rise. The Albian deposits in the Ialomița-Dâmbovița area are genetically and stratigraphically correlated with the deposits of the Babele Sandstone and the Scropoasa-Lăptici Sandstone units in the Bucegi Mountains. The Babele-Dâmbovița sedimentary basin is distinct and different from the depositional basin of the deep-water Albian conglomerate fan from the Carpathian Bend zone.